Предмет: Алгебра,
автор: Lenka1381
Помогите, пожалуйста.
Приложения:

Ответы
Автор ответа:
1
Объяснение:
x^2 × (2x^2 - 5x +3) = 0
x^2×(2x^2-2x-3x+3)=0
x^2×(2x×(x-1) -3x+3) = 0
x^2(2x×(x-1)-3(x-1))=0
x^2×(x-1)(2x-3) = 0
x^2 = 0
x-1 = 0
2x-3=0
x=0
x-1=0
2x-3=0
х1=0, х2=1, х3=3/2
rrtiws:
сделай пж лучшим ответом
Похожие вопросы
Предмет: Математика,
автор: julyayana
Предмет: Математика,
автор: dmitruk8
Предмет: Химия,
автор: Саяе32
Предмет: Математика,
автор: Лольник3462
Предмет: Химия,
автор: vampair5